2003
DOI: 10.2527/2003.81123028x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flax supplementation and a combined trenbolone acetate and estradiol implant on circulating insulin-like growth factor-I and muscle insulin-like growth factor-I messenger RNA levels in beef cattle1,2

Abstract: We evaluated effects of a 5% (dry matter basis) ground flaxseed supplement (flax) and a trenbolone acetate and estradiol-17beta implant, Revalor-S, on circulating IGF-I and muscle IGF-I messenger RNA (mRNA). Sixteen crossbred yearling steers (initial BW = 397 kg) were assigned randomly to one of four treatments: 1) flax/implant; 2) nonflax/implant; 3) flax/nonimplant; and 4) nonflax/nonimplant. Serum was harvested from blood collected on d 0 (before implant or flax addition), 14, and 28, and used in subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…In the present study, a diet supplemented with flaxseed did not affect IGF concentration in either follicular fluid or plasma. In agreement with our findings, another study [36] also reported that plasma IGF-I concentrations in beef steers fed 5% ground flaxseed were not different from that of steers fed a control diet. Similarly, in lactating dairy cows fed a protected form of whole flaxseed, plasma IGF-I concentrations did not differ from that of cows fed a diet with no added fat [9].…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, a diet supplemented with flaxseed did not affect IGF concentration in either follicular fluid or plasma. In agreement with our findings, another study [36] also reported that plasma IGF-I concentrations in beef steers fed 5% ground flaxseed were not different from that of steers fed a control diet. Similarly, in lactating dairy cows fed a protected form of whole flaxseed, plasma IGF-I concentrations did not differ from that of cows fed a diet with no added fat [9].…”
Section: Discussionsupporting
confidence: 82%
“…After d 28, IGF-I concentrations returned to near d 0 (96.9 ng/mL) concentrations in the winter, but remained elevated above d 0 (60.6 ng/mL) concentrations during the summer, although mean IGF-I concentration from d 28 through d 84 were similar in winter (108.1 ng/mL) and summer (102.7 ng/mL). Dunn et al (2003) reported increases in sera IGF-I concentrations of 52 and 84% because of using growthpromoting implants in steers. In that study, the 28-d gain response to implanting ranged from 0.52 to 0.97 kg/d.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that the Pampusch et al (2003) study was a comparison within steer (i.e. d 0 to d 7) and the Dunn et al (2003) study compared implanted to non-implanted steers, which could explain differences in the final expression between studies. Pampusch et al (2003) observed that IGF-1 expression Dunn et al (2003) showed that, although IGF-1 in circulation increased as early as 14 d post-implantation, mRNA expression of IGF-1 in the muscle did not increase until d 28 and was 2.4 fold greater in implanted calves than non-implanted calves at that time.…”
Section: Resultsmentioning
confidence: 99%
“…d 0 to d 7) and the Dunn et al (2003) study compared implanted to non-implanted steers, which could explain differences in the final expression between studies. Pampusch et al (2003) observed that IGF-1 expression Dunn et al (2003) showed that, although IGF-1 in circulation increased as early as 14 d post-implantation, mRNA expression of IGF-1 in the muscle did not increase until d 28 and was 2.4 fold greater in implanted calves than non-implanted calves at that time. This latter study demonstrates that an increase in serum IGF-1 may be observed without an increase in hepatic IGF-1 expression, as noted in the present study.…”
Section: Resultsmentioning
confidence: 99%